2000
DOI: 10.1093/rheumatology/39.1.67
|View full text |Cite
|
Sign up to set email alerts
|

Genotype–phenotype correlation in a large group of Turkish patients with familial Mediterranean fever: evidence for mutation-independent amyloidosis

Abstract: None of the four missense mutations is associated with a severe disease or the development of amyloidosis in Turkish FMF patients living in Turkey. The influence of unknown environmental factors and/or the presence of other genetic changes are necessary to explain the phenotypic variation of the disease and the development of amyloidosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
71
4
21

Year Published

2001
2001
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 153 publications
(110 citation statements)
references
References 22 publications
14
71
4
21
Order By: Relevance
“…31,32 Unexpectedly though, the presence of M694V was not found to be associated with a severe form of the disease or the development of amyloidosis in an independent series from Ankara. 33,34 This group recently reported that patients with the G138 polymorphism in exon 2 were more prone to amyloidosis. 35 Other mutations at codon 694 and mutation M680I are also possibly severe ones.…”
Section: Allelic Heterogeneitymentioning
confidence: 99%
See 2 more Smart Citations
“…31,32 Unexpectedly though, the presence of M694V was not found to be associated with a severe form of the disease or the development of amyloidosis in an independent series from Ankara. 33,34 This group recently reported that patients with the G138 polymorphism in exon 2 were more prone to amyloidosis. 35 Other mutations at codon 694 and mutation M680I are also possibly severe ones.…”
Section: Allelic Heterogeneitymentioning
confidence: 99%
“…23 V726A prevalence is generally higher in populations with mild disease, 3,40,42 but genotypes including this mutation may be found in patients with amyloidosis. 33,34 In one Jordanian series however, genotypes including V726A were associated with a more severe disease than those with M680I. 43 Mild phenotype or incomplete penetrance have also been described in patients with K695R or P369S.…”
Section: Allelic Heterogeneitymentioning
confidence: 99%
See 1 more Smart Citation
“…3,5,[9][10][11][12][13][14][15][16]20,21 The most common mutation characterized in Turks is the M694V mutation with the frequency of 30-50%. The E148Q mutation occurs at a frequency ranging from 1.4-11.4% according to some previous studies.…”
Section: Patient Genotypesmentioning
confidence: 99%
“…2,7 Gene sequence and phenotypic characteristics of FMF patients change according to geographic regions, which include people from certain ethnic origins both in Turkey and in the World. 1,2,[7][8][9][10][11][12][13][14][15][16][17] Unfortunately, there is a paucity of studies that have investigated the genotypic and phenotypic variations of FMF patients in southeast Turkey. 3 Therefore, we aimed to investigate the genotypic and phenotypic characteristics of children with FMF in southeastern Turkey.…”
Section: Introductionmentioning
confidence: 99%